Green synthesis of zero-valent iron nanoparticles from cape gooseberry (physalis peruviana l.) Biomass for oil spill remediation - Amina Nalweyiso; Christine Betty Nagawa; Emel Yildiz; Serkan Uzman; Joshua Wanyama; John Baptist Kirabira; Ahmed Zziwa; Farad Sagala; Patrick Ssebugere; Solomon Omwoma; Christine Kyarimpa; Nicholas Kiggundu; et al. (Environmental Challenges)
The study explores eco-friendly synthesis of zero valent iron nanoparticles (nZVI) using Cape gooseberry fruit, leaf or husk extracts as reducing agents for iron (III) chloride (0.5 M, 0.1 M or 0.01 M) precursor in a 2:1 ratio under sonication. The nZVI were characterized using ultraviolet-visible (UV–vis) spectroscopy, Fourier transform-infrared (FTIR) spectroscopy, X-ray diffraction (XRD), Scanning electron microscopy (SEM), Zetasizer analysis, and Brunauer-Emmett-Teller (BET) analysis. Batch remediation experiments for 1 ml, 5 ml, or 10 ml of diesel in 100 ml of deionized water were performed using 0.33 g of nZVI. The highest quantity of nZVI was obtained from 0.5 M FeCl3 and fruit extract. FTIR and UV–vis spectroscopy confirmed that Cape gooseberry polyphenols reduced and stabilized the nZVI, while XRD indicated a crystalline alpha-iron core with iron oxide shells. SEM imaging revealed agglomeration in nZVI from fruit and leaf extracts, while husk extract nZVI showed uniform size and porosity. Zytasizer analysis showed nZVI from fruit extract had diameters under 100 nm, while leaf and husk extracts nZVI were slightly over 100 nm. Zeta potentials were -29.48 mV (fruit), -33.62 mV (leaf), and -33.5 mV (husk). BET analysis showed husk extract nZVI had the highest surface area. The synthesized nZVI achieved diesel remediation efficiencies of 94.3 % (fruit), 94.3 % (leaf), and 94.6 % (husk) demonstrating successful synthesis of nZVI for diesel contamination cleanup. In addition to being a waste material, husks are advantageous over the fruits and leaves as feedstock for nZVI synthesis due to their superior uniformity and surface area.